Enhanced 5G contender based flat top weighted window communication systems - Omar Abdulkareem Mahmood; Yousif I. Hammadi (Bulletin of Electrical Engineering and Informatics, 2022)
To create a new transmission phenomenon, the availability of good data rates, the development of the internet of things (IoT), and different machine type communications (MTC) developed the ability to converse without synchronization, or the need for routing overhead in the form of synchronization overhead, while using mixed legacy fourth generation (4G) systems, based on orthogonal frequency division multiplexing, cannot meet these requirements (OFDM). Many waveform alternatives for OFDM have been proposed, including FBMC, GFDM, UFMC, and filtering-OFDM, in order to meet the criteria of the next generation system F-OFDM. As a consequence, a revolutionary filter based on a flat top weighted window is described in this work, where simulation results indicate that the suggested method outperforms prior designs in regard to spectral adeptness increased substantially acrros the deminish in the required side-information as overhead of the synchronization process. The trasitional F-OFDM uses root-raised-cosine filter. However, in this paper, novel filter design was proposed, whis is simple and real-time construction capability. This new filter is built around legacy filters, where the new filter is a combination of different filters to make use of various advantages of the old filters and get rid of the disadvangages. The power spectral density (PSD), -157.2 dBW/Hz, which is outstanding CP-OFDM-PSD, -50 dBW/Hz.